Atom Transfer Radical Polymerization and Its Continuous Processes - Shen, Youqing (My University, 2001)
Atom transfer radical polymerization (ATRP), a transition metal-mediated living radical polymerization, has been developed as a powerful tool for synthesizing polymers of controlled structure, but its catalyst residue remains challenging. Described in this thesis is a comprehensive study on the ATRP applications in macromonomer preparation and the solutions to its catalyst residue problem by catalyst supporting. A novel continuous process for the production of polymers and block copolymers with controlled molecular weights has also been developed using packed column reactor technologies. New versatile vinyl-containing initiators, 2'-vinyloxyethyl 2-bromoisobutyrate (VBIB) and 3'-vinyloxylpropyl trichloroacetamide (VTCA), were screened for the macromonomer synthesis of different vinyl monomer types by ATRP. Polymethacrylate and polystyrene macromonomers of well-controlled molecular weights were obtained without consumption of the initiators' vinyl moieties at monomer conversions lower than 80%. However, the ATRP of acrylates started to consume the vinyl moieties at medium conversions. Therefore, the polymerization of acrylates must be terminated at an early stage in order to obtain their macromonomers. Three catalyst supporting systems have been developed to solve the catalyst contamination problem for batch ATRP. Firstly, the CuBr/HMTETA complex was supported onto silica gel by physical adsorption for ATRP of MMA in toluene. The supported complex mediated a living polymerization of MMA. The recycled catalysts had a high retention of catalyst activity and improved control over the polymer molecular weights. Secondly the catalyst was immobilized on silica gel by covalent bonding for polar solvent/monomer systems. In this supporting method, the supporting spacer length was found to strongly affect the catalyst activity and control of the polymerization. The catalyst supported via three-unit PEG had highest activity and regulated the polymerization best. Longer or shorter spacer deteriorated catalyst activity and control of polymerization. Thirdly, the catalyst was grafted onto soluble and recoverable PE and PE-b-PEG supports to overcome the adverse effects of insoluble support. Catalyst directly grafted on the long PE chains had low activities, poor control over polymerization and low retention of the catalyst activity upon recycling. Using PEG as spacer to graft the catalyst onto the PE support minimized these adverse effects of the PE support. PE₂₅-PEG₄-TEDETA-CuBr effectively mediated the ATRP of MMA, and retained 90% activity of the fresh catalyst upon recycling with good polymer molecular weight control. Catalyst recycling for batch ATRP was found laborious and time-demanding. A continuous ATRP using column reactors packed with silica gel supported CuBr/HMTET A was developed for homo- and block-copolymerization of MMA. The reactor showed good stability in both catalyst activity and molecular weight control of resulting PMMA. The polymerization in the reactor was still a living process. Thus, adjusting the MMA flow rate, which determined the monomer conversion, readily changed the molecular weight of PMMA. The block copolymerization of MMA with nbutyl methacrylate (nBMA) was carried out using two reactors in series. The produced block copolymers had little contamination of PMMA prepolymer. The chain length of nBMA block could be adjusted by the flow rate of nBMA in the second reactor.
Keywords: Chemical Engineering; Chemical Engineering